Exploration of multiple enhancing pathways of digital economy development of city clusters using fuzzy-set qualitative comparative analysis - Cong, Xuhui; Liu, Bocong; Wang, Liang; Su, Peikun; Zhang, Shenghui; Liu, Yijia; Ustinovičius, Leonas; Skibniewski, Miroslaw J. (Technological and Economic Development of Economy, 2024)
As a crucial catalyst for worldwide economic expansion, the digital economy (DE) has garnered widespread attention and has been regarded as crucial for the promotion of economic growth and innovation. The development of the DE brings both significant opportunities and challenges to city clusters. It enhances urban competitiveness, improves residents’ quality of life, and strengthens urban governance, which is of great significance for the development of city clusters. In this context, although previous studies comprehensively analyzed the advancement of the DE of certain cities and revealed their strategies, challenges, and successful experiences in the development of their DE, research on the determinants and enhancing pathways of the digital economy development of city clusters (DEDCC) is scant. As the core node of DE development, city clusters, as well as their potential and influence, cannot be ignored. Therefore, this study investigates the Shandong Peninsula Urban Agglomeration in China, constructs a theoretical analysis framework for the DEDCC, and utilizes fsQCA (Fuzzy-set Qualitative Comparative Analysis) to examine the complex causal processes of the DEDCC. The fsQCA method is utilized from a configurational perspective to explore the complex driving mechanisms of DEDCC. The objective is to investigate the pathways for enhancing DEDCC and provide insights for the DE development of other city clusters. Results reveal the following: (1) the reciprocal collaboration between market factors and fundamental factors should be examined to accelerate the high-quality DEDCC. (2) technological innovation (TI) capacity is a crucial determinant of the high-quality DEDCC. (3) the coordinated development of the market, the foundation, and TI should be prioritized to achieve the high-quality DEDCC.